2009
DOI: 10.2174/1874196700902010163
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Formation on Lipid Membrane Surfaces

Abstract: Several lines of research have concluded lipid membranes to efficiently induce the formation of amyloid-type fibers by a number of proteins. In brief, membranes, particularly when containing acidic, negatively charged lipids, concentrate cationic peptides/proteins onto their surfaces, into a local low pH milieu. The latter together with the anisotropic low dielectricity environment of the lipid membrane further forces polypeptides to align and adjust their conformation so as to enable a proper arrangement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 111 publications
2
69
0
Order By: Relevance
“…Only small nonsystematic changes of the 13 C chemical shift of the COOH group in PazePC (less than 0.5 ppm) are observed as a function of solvent pH. The significant 4−5 ppm increase in carboxyl chemical shift related to deprotonation 35 is therefore not detected (see Materials and Methods) supporting the conclusion that PazePC molecules adopted the same protonation state in all distinct samples.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Only small nonsystematic changes of the 13 C chemical shift of the COOH group in PazePC (less than 0.5 ppm) are observed as a function of solvent pH. The significant 4−5 ppm increase in carboxyl chemical shift related to deprotonation 35 is therefore not detected (see Materials and Methods) supporting the conclusion that PazePC molecules adopted the same protonation state in all distinct samples.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…The following experimental setups were used. 13 C DP Experiments. Radio frequency pulses were performed with the following nutation frequencies: 80.65 kHz ( 13 C 90°) and 40 kHz (TPPM 1 H decoupling pulses).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble oligomers of the peptide, formed as an intermediate state in this process of amyloidogenesis, induces permeabilization of the cancer cell membrane, leading to the death of these cells via apoptosis and necrosis . Both experimental and theoretical studies have suggested that similar PS‐mediated mechanisms of anticancer action may be used by other amyloidogenic host defense peptides …”
Section: Membrane‐based Factors That Contribute To the Anticancer Actmentioning
confidence: 99%
“…SAAPs utilize mechanisms of antimicrobial action that are non-membranolytic and involve the internalization of these peptides to attack intracellular targets [33], and similar non-membranolytic antimicrobial mechanisms have been proposed for a number of other AMPs [166][167][168], such as the synthetic peptide, WRWYCR, which targets bacterial DNA repair mechanisms [169]. Amyloid-mediated mechanisms of antimicrobial action have been reported for a variety of other AMPs (Chapter 4) [171][172][173][174][175][176][177] such as protegrin-1 from pigs [69]. Amyloid-mediated mechanisms of antimicrobial action have been reported for a variety of other AMPs (Chapter 4) [171][172][173][174][175][176][177] such as protegrin-1 from pigs [69].…”
Section: Aamps and Their Structure-function Relationshipsmentioning
confidence: 99%